Pain problem in patients in palliative home care - Karol Czernecki; Barbara Ślusarska (Kazimierz Wielki University, 2022)
Aim of the study: The aim of the study is to determine the intensity and nature of pain and treatment methods, as well as to assess the patient's sense of comfort in palliative care in the home environment.   Material and methods: Research using the diagnostic survey method, using the PAPI (Paper & Pen Personal Interview) technique, was carried out among patients in palliative care provided by the home care team in March and April 2022. The study included 55 palliative patients under the care of the home palliative care team in the following cities: Warszawa, Kraków, Sosnowiec and the poviats of Stalowa Wola, Tarnobrzeg and Sandomierz. Results: Of the 55 patients studied, the majority of 50.9% (n = 28) were men. The vast majority of 90.9% (n = 50) of people replied that pain was present, but patients were taking pain medications. Pain in the majority of patients, 65.5% (n = 36), it was felt at any time during the day. On the NRS scale, pain intensity ranging from 4 to 7 points was assessed by 61.8% of patients. Among the symptoms associated with pain, patients indicated the following as very severe: fatigue and weariness (63.6%), drowsiness (41.8%), nervousness (40.0%), depression (38.2%), difficulty concentrating (32.7%), lack of energy, weakness (30.9%), worry (36.4%), apathy (36.4%), dry mouth (34.5%). The average result on the comfort scale in the group of patients is M = 34.50; SD = 5.04. There was a statistically significant correlation between satisfaction with care and the level of perceived comfort (p = 0.014). Conclusions: In the group of palliative patients treated at home, "pain" is one of their main ailments. Most patients take painkillers to reduce or completely eliminate the pain. However, the symptoms associated with it remain. Patients who strongly indicated satisfaction with care had a significantly higher level of comfort compared to other patients